The body and the pencil. Ten questions to Claudio Patané - Nucifora, Sebastiano (DISEGNARECON, 2014)
The relevance of matter in drawing. The body weight of the designer and his/her tools, the color stains in his/her fingers after s/he uses them. The sound of footsteps all over the place. The need to know, the desire to remember and cherish, but also to forget. The freedom to get lost while wandering around, notebook in hand and no street sign to rely on. Life drawing not meant as an ancient ritual, but as a necessary practice connecting people with the third dimension. Ten questions to urban sketcher Claudio Patane share with the reader the experiences and point of view of a true wandering inquirer - among other things - of the urban scene. An artist working with paper and pencil in the digital age, in search of a different approach to digital technology: critical but not hostile, open to the social values of sharing and yet aware of the dangers concealed in its possible self-referential drift.